Development of sustainable and thermally activated nano cementitious composites containing graphene oxide and phase change materials: Tensile, pore structure and microstructural evaluation - Yildirim, Pinar; Erdem, Savas; Uysal, Mucteba (ELSEVIER, 2026)
Reducing energy consumption, which is rapidly increasing due to technological development and urbanization, has become a major research focus in the construction sector. The high share of buildings in total energy consumption highlights the importance of this issue, while the demand for high-strength concrete continues to increase with advances in construction technologies. While meeting these increasing demands, reducing CO2 emissions associated with cement production, which is indispensable to the construction industry, has also become a key research priority. In the 21st century, studies aiming to produce higher-strength cement-based composites using reduced cement content have increasingly focused on nanomaterials. In this context, this study investigates the tensile strength, pore structure, and microstructural properties of cementbased composites incorporating microencapsulated phase-change materials (PCM) and nanographene oxide (NGO). It has been possible to contribute to the limited data on tensile strength. The axial tensile strength of PCM-containing composites was determined experimentally, and a decrease in tensile strength was observed with increasing PCM content. To compensate for this decrease, the positive contribution of NGO added to the mixtures to tensile strength was quantitatively demonstrated. Furthermore, the thermal conductivity and microstructural properties of the samples were determined. In addition, offering an innovative approach, fractal dimension values were calculated through imaging performed on the fracture surfaces of the samples. The relationship between PCM ratio and fractal dimension was revealed. The experimental results and analyses show that the combined use of PCM and NGO can potentially reduce CO2 emissions from buildings in terms of construction and operation.
Keywords: Sustainable building materials; Phase change materials; Microcapsule; Nanographene-oxide; Tensile strength; Fractal analysis; Porosimetry; MECHANICAL-PROPERTIES; CONCRETE; DURABILITY; BEHAVIOR; DESIGN; Chemistry; Science & Technology - Other Topics; Environmental Sciences & Ecology